Healthy lifestyle, glucose level and BMI in adults from the Amauta Valley - Ate Vitarte - Lima – 2020 - Hurtado Casanca, Carla (2020)
Objective: To determine the relationship between healthy lifestyles, glucose and BMI in adults from theAmauta Valley - Ate Vitarte - Lima - 2020. Methodology: Non-experimental design, quantitative, crosssectionaland correlational approach. The sample is made up of 175 adults of both sexes betweenthe ages of 18 and 64 years. Data were collected through a lifestyle questionnaire; Furthermore,anthropometric measurements such as weight and height were taken to determine the Body MassIndex (BMI), and the glucose level was also evaluated. Results: 82.7% of the evaluated populationpresented a healthy lifestyle and only 17.7% an unhealthy condition; likewise, 77.2% did not performphysical activity, finding that 52.6% performed light activity. Regarding the consumption of alcohol andother drugs, 94.2% are healthy; Also, 76.0% reported having adequate sleep and 24.0% had poor sleep quality. Regarding eating habits, 81.2% are healthy, a group of 18.9% does not have healthyhabits, and 68.0% did not have self-care. It was found that 42.3% had diabetes. Finally, 34.3% hada normal BMI, 42.3% were overweight, and 23.4% were obese. Conclusion: There is a relationshipbetween the lifestyle, glucose levels and BMI of the participants. In addition, the study shows that lackof physical activity is related to increased BMI, which in turn is associated with elevated glucose levels.Therefore, if a modification of the lifestyle, physical condition and sports, recreation and free timemanagement, consumption of alcohol and other drugs, sleep, eating habits and self-care, and medicalcare is made, it can be of great help to the prevention of metabolic diseases.